Controlled Ring-Opening Polymerization of O-Carboxyanhydrides to Synthesize Functionalized Poly(α-Hydroxy Acids) - Wang, Xiaoqian; Chin, Ai Lin; Tong, Rong (Organic Materials, 2021)
Poly(α-hydroxy acids), as a family of biodegradable polyesters, are valuable materials due to their broad applications in packaging, agriculture, and biomedical engineering. Herein we highlight and explore recent advances of catalysts in controlled ring-opening polymerization of O-carboxyanhydrides towards functionalized poly(α-hydroxy acids), especially metal catalyst-mediated controlled polymerization. Limitations of current polymerization strategies of O-carboxyanhydrides are discussed.
Keywords: polyesters; O-carboxyanhydrides; ring-opening polymerization; poly(α-hydroxy acids); stereoselective polymerization; electrochemical polymerization